Validation gas chromatography-fid method for analysis of ethanol content in vinegar - Indah Noviyanti Ruhmana Pulungan; Sugijanto Kartosentono; Amirudin Prawita (Universitas Airlangga, 2018)
Production process of vinegar could be synthesized by chemical or microbiological. In Islam, vinegar must not be consumed if contains ethanol ≥ 1%, because it is categorized into khamr. The maximum concentration of vinegar fermentation is 1,0 %. This research was to analyze the alcohol compund that consist in vinegar. The validation method that used in this study are: selectivity, linearity, range, precision, accuracy, LOD and LOQ. The analysis instrument was gas chromatography Agilent 6890 Series GC System, with a Flame Ionization Detector (FID) and a column HP-5 (5% Phenyl 95% Methyl Siloxane), and optimal conditions were obtained by using temperature of inlet and detector of 250°C whilst the temperature of oven programed initially at 40°C, hold for 5 minutes, and raised to 5°C/min to 200°C. were used in this study. For split ratio was achieved at 50:1 and the injection volume was 1.0µl. The methods were proven selective and demonstrated linearity, precision and accuracy with r = 0.9995; 5,63% and 101,25%, respectively. On the other hand, the methods were proven that the sample contains alcohol. Finally, the result of quantitative ethanol contents analysis in vinegar from Saudi Arabia is 2,28.10-2 % v/v; and vinegar brand “x” from market in Surabaya is 1,17.10-2 v/v.